The return to recognition of prior learning: an analysis of the Portuguese case - Sgobbi, Francesca (2020)
In the first decade of this century subsequent Portuguese governments promoted two large programmes (RVCC Centres, 2001-2005, and Novas Oportunidades, 2006-2010) aimed at improving the educational qualifications of the adult population by means of an extended network of centres in charge of apprising prior and experiential learning. Based on the Quadros de Pessoal survey this paper assesses the wage return to the recognition of prior learning promoted by the RVCC Centres and the Novas Oportunidades programmes by means of DID-PSM estimates. The outcomes of the empirical analysis outline non-negative wage effects from participation in recognition of prior learning compared to traditional formal adult education. However, the path undertaken to upgrade individual qualification matters. Participation in recognition of prior learning under the RVCC Centres initiative resulted in no significant wage increases compared to formal adult education, whereas differentials became mostly positive and statistically significant under the Novas Oportunidades programme.